Practical experience in teaching inventory management with edublogs - Julio J. Garcia-Sabater; Pilar I. Vidal-Carreras; Cristina Santandreu; Rosario Perello-Marin (Journal of Industrial Engineering and Management (JIEM), 2011)
Purpose: The aim of this paper is to analyze the utility of edublogs in teaching-learning process applied to postgraduate Courses. Particularly, it describes an experience carried out while delivering a Course offered to students, mainly Industrial Engineers, of a certain Master program. Design/methodology/approach: In the first section of the paper, we perform a literature review with the aim of defining some basic concepts as blog, weblog or edublog. Later on, we compare some educational models to identify best practices related to new technologies, and particularly, to edublogs. Finally, we analyze our experience in a postgraduate Course. Findings and Originality/value: We have identified best practices on teaching using edublogs and we have applied them to a particular postgraduate Course. Research limitations/implications: Conclusions are obtained from only one experience (one postgraduate Course). We intend to extend the analysis to more postgraduate Courses and compare the obtained results. Practical implications: We have applied the previously described methodology and we have discussed advantages and disadvantages of using edublogs.
Keywords: 650; blogs; edublogs; learning; inventory management